Two-dimensional TiOx nanostructures on Au(111): a scanning tunneling microscopy and spectroscopy investigation. (23rd November 2015) - Tumino, F; Carrozzo, P; Mascaretti, L; Casari, C S; Passoni, M; Tosoni, S; Bottani, C E; Bassi, A Li
Abstract: We investigated the growth of titanium oxide two-dimensional nanostructures on Au(111), produced by Ti evaporation and post-deposition oxidation. Scanning tunneling microscopy and spectroscopy (STM and STS) and low-energy electron diffraction measurements characterized the morphological, structural and electronic properties of the observed structures. Five distinct TiO x phases were identified: the honeycomb and pinwheel phases appear as monolayer films wetting the gold surface, while nanocrystallites of the triangular, row and needle phases grow mainly over the honeycomb or pinwheel layers. Density Functional Theory investigation of the honeycomb structure supports a structural model based on a Ti-O bilayer having Ti 2 O 3 stoichiometry. The pinwheel phase was observed to evolve, for increasing coverage, from single triangular crystallites to a well-ordered film forming a superstructure, which can be interpreted within a moiré-like model. Structural characteristics of the other three phases were disclosed from the analysis of high-resolution STM measurements. STS measurements revealed a partial metallization of honeycomb and pinwheel and a semiconducting character of row and triangular phases.